Global ideas against racism: From a journey of ideas to a digital future workshop - Suh, Hanna; Kato, Jotaro; Abay, Robel Afeworki; Denk, Albert (Momentum Quarterly, 2024)
Within the framework of the project “Global ideas against racism,” we applied the method of the future workshop to anti-racism work. The method includes a three-step process of problem analysis, utopia development, and the concretization of an implementation plan. In particular, the work with utopias can be interpreted as progressive as it generates knowledge that is more detached from expectations and ordinary thought patterns. By applying it in our project, we have broken new ground in the field of anti-racism work while at the same time upscaled the method so that it works on a more global level. In addition, we recognized and critically reflected on the power relations that exist within academic knowledge production and have therefore subsequently handed the power over to the participants. The digital implementation brought the advantage of including a more extensive range of participants and better access facilitation. Going forward, we recommend a hybrid form for future applications, including on-site workshops. The method application in the field of anti-racism engagements proved to be particularly fruitful, resulting in four concrete implementation projects.
Keywords: Anti-Racism; Future Workshop; Participatory Approach; Global Perspectives; Digital Intervention